The association of psychological stress with metabolic syndrome and its components: cross-sectional and bidirectional two-sample Mendelian randomization analyses - Li, Cancan; Tao, Tianqi; Tang, Yanyan; Lu, Huimin; Zhang, Hongfeng; Li, Huixin; Liu, Xiuhua; Guan, Weiping; Niu, Yixuan (Frontiers in Endocrinology, 2023)
Background: Metabolic syndrome (MetS) is a group of co-occurring conditions that increase the risk of cardiovascular disease, which include the conditions of hypertension, overweight or obesity, hyperglycaemia, and dyslipidaemia. Psychological stress is gradually being taken seriously, stem from the imbalance between environmental demands and individual perceptions. However, the potential causal relationship between psychological stress and MetS remains unclear. Method: We conducted cross-sectional and bidirectional Mendelian randomization (MR) analyses to clarify the potential causal relationship of psychological stress with MetS and its components. Multivariable logistic regression models were used to adjust for potential confounders in the cross-sectional study in Chinese population included 4,933 individuals (70.1% men; mean age 46.13 ± 8.25). Stratified analyses of sexual characteristics were also performed. Bidirectional MR analyses were further carried out to verify causality based on summary level genome-wide association studies in European population, using main analysis of inverse variance weighted method. Results: We found that higher psychological stress levels were cross-sectionally associated with an increased risk of hypertension in men [odds ratio (OR),1.372; 95% confidence interval (CI), 1.044-1.802; P = 0.023]; moreover, higher levels of hypertension were cross-sectionally associated with an increased risk of psychological stress in men and the total population (men: OR, 1.517; 95%CI, 1.129-2.184; P = 0.007; total population: OR, 1.343; 95%CI, 1.036-1.741; P = 0.026). Genetically predicted hypertension was causally associated with a higher risk of psychological stress in the inverse-variance weighted MR model (OR, 2.386; 95% CI, 1.209-4.710; P = 0.012). However, there was no association between psychological stress and MetS or the other three risk factors (overweight or obesity, hyperglycaemia, and dyslipidaemia) in cross-sectional and MR analyses. Conclusion: Although we did not observe an association between psychological stress and MetS, we found the associations between psychological stress and hypertension both in cross-sectional and MR studies, which may have implications for targeting hypertension-related factors in interventions to improve mental and metabolic health. Further study is needed to confirm our findings.